HPV knowledge gaps and information seeking by oral cancer patients. (December 2016) - Inglehart, R.C.; Taberna, M.; Pickard, R.K.L.; Hoff, M.; Fakhry, C.; Ozer, E.; Katz, M.; Gillison, M.L.
Highlights: Despite high health literacy, oral cancer patients exhibited gaps in HPV knowledge. HPV-positive patients knew more than HPV-negative, but still had knowledge gaps. Many patients felt they did not know enough to discuss HPV with their doctor. Doctors were highly trusted but infrequently used as information sources. Abstract: Objectives: The incidence of human papillomavirus (HPV) positive oral squamous cell carcinoma (OSCC) continues to increase over time, challenging healthcare providers to address their patients' HPV-related concerns. Materials and methods: This prospective study assessed health literacy, HPV knowledge, utilization and trust in information sources among patients with incident HPV-positive or HPV-negative OSCC diagnosed at the Ohio State University from 2011 to 2015. Health literacy was assessed with a standardized scale. Additional questions evaluated HPV knowledge (including transmission, prevalence, health consequences and treatment), the frequency and type of information sources sought, and trust in those sources. Results: Surveys were collected from 372 OSCC cases (HPV-positive, n = 188; HPV-negative, n = 184). Despite high mean health literacy scores, only 45.2% of HPV-related knowledge questions were answered correctly. HPV was known to be a sexually transmitted infection and a cause of cervical and anal cancer by 66.0%, 56.5% and 15.2%, respectively. In all domains, cases with HPV-positive OSCC were significantly more informed than HPV-negative cases (for all, p < 0.01). Only 52.7% and 56.2% of patients with HPV-positive OSCC felt they knew enough to be comfortable discussing HPV with their doctor or sexual partner, respectively. The most frequently used information source was the internet (80.9%), which ranked 8th in trust of 15 possible sources. Although most (95.5%) patients trusted information from their doctors, only 37.9% used doctors as an information source. Conclusions: Doctors are a highly trusted, but infrequent utilized, information source and should facilitate patient access to high-quality HPV information sources.